2016
DOI: 10.1371/journal.pone.0166956
|View full text |Cite
|
Sign up to set email alerts
|

Role of PTEN in Oxidative Stress and DNA Damage in the Liver of Whole-Body Pten Haplodeficient Mice

Abstract: Type 2 diabetes (T2DM) and obesity are frequently associated with non-alcoholic fatty liver disease (NAFLD) and with an elevated cancer incidence. The molecular mechanisms of carcinogenesis in this context are only partially understood. High blood insulin levels are typical in early T2DM and excessive insulin can cause elevated reactive oxygen species (ROS) production and genomic instability. ROS are important for various cellular functions in signaling and host defense. However, elevated ROS formation is thou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 42 publications
2
29
0
Order By: Relevance
“…In the current study, we demonstrated that hepatic TC and TG contents were significantly reduced after treatment with rmTSG-6, and liver histology using H&E and oil red O staining further supported the alleviation of hepatic steatosis by TSG-6 treatment. Oxidative stress plays a critical role in the pathogenesis of ALD, as numerous studies reported that formation of reactive oxygen species (ROS) are crucial for the progression of ALD (Leung and Nieto, 2013;Bankoglu et al, 2016), because they could induce hepatic steatosis, inflammatory cell infiltration, hepatomegaly, fibrosis and cirrhosis (Li et al, 2014). In this study, we found that treatment with rmTSG-6 caused significant increment in hepatic GSH level but reduction in hepatic MDA, both of which were markers of oxidative stress.…”
Section: Discussionmentioning
confidence: 56%
“…In the current study, we demonstrated that hepatic TC and TG contents were significantly reduced after treatment with rmTSG-6, and liver histology using H&E and oil red O staining further supported the alleviation of hepatic steatosis by TSG-6 treatment. Oxidative stress plays a critical role in the pathogenesis of ALD, as numerous studies reported that formation of reactive oxygen species (ROS) are crucial for the progression of ALD (Leung and Nieto, 2013;Bankoglu et al, 2016), because they could induce hepatic steatosis, inflammatory cell infiltration, hepatomegaly, fibrosis and cirrhosis (Li et al, 2014). In this study, we found that treatment with rmTSG-6 caused significant increment in hepatic GSH level but reduction in hepatic MDA, both of which were markers of oxidative stress.…”
Section: Discussionmentioning
confidence: 56%
“…Oxidant stress plays a dominant role in the pathogenesis of ALD, as multiple studies have shown that generation of ROS is key for the progression of fatty liver to steatohepatitis and cirrhosis [23,24,25,26,27]. They induce pathological changes such as steatosis, inflammatory cell infiltration, hepatomegaly, fibrosis and cirrhosis [28].…”
Section: Key Players In Aldmentioning
confidence: 99%
“…One mechanism by which ROS exert cellular effects is through the regulation of target molecules, including PI3K/AKT/PTEN (39). The PI3K/AKT/PTEN signaling pathway protects against damaging effects originating from high levels of insulin (40). In addition, the PI3K/AKT/PTEN signaling pathway regulates factors involved in cell survival and proliferation ( Fig.…”
Section: Pten In the Anti-oxidative Machinerymentioning
confidence: 99%
“…In addition, the PI3K/AKT/PTEN signaling pathway regulates factors involved in cell survival and proliferation ( Fig. 2) (40). PTEN is a dual specificity phosphatase, processing lipids and proteins, and it is a member of the protein tyrosine phosphatase family of phosphatases (41,42).…”
Section: Pten In the Anti-oxidative Machinerymentioning
confidence: 99%